In the path of the ancestresses : a philosophical exploration of mana wahine Maori : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Philosophy at Massey University - Wyse, Rosemary Therese (Massey University, 1992)
Some customs and beliefs within Maori tradition appear to countenance a view of the subordinate status of Maori women. For instance, it is customary for women to sit at a lower level than men during formal occasions on the marae. There is also a general belief that while men are tapu (frequently translated as meaning sacred) women are tapu only in "special circumstances" (Schwimmer 1966:20). In a similar vein, it is claimed that moral and spiritual matters are the prerogative of Maori males while Maori women are responsible for the physical or material aspects of life (Barlow 1991:147-148). I intend to establish that if Maori ethics is based on precedent (Patterson 1992:155) then the view of Maori women as a group being subordinate to their men is inappropriate. The deeds of the ancestors, handed down through the generations within the traditional narratives, provide the models for correct behaviour. These models do not support a view of female inferiority but confirm a female status and authority which is equal to but different from that attributed to males. It is, I believe, unnecessary to the purpose of this thesis to challenge the metaphysical aspects of the Maori world view. As a Pakeha using Western philosophical techniques to explore Maori concepts, it would be inappropriate for me to do so. More importantly for this writer, there are many Maori women who regard traditional, spiritually based customs and beliefs as the means by which they and their families may retain Maori cultural identity. My aim is to establish that even in traditional terms, the notion of female subordination runs counter to the ethical ideals established by the ancestors and ancestresses. I will argue that a distinctively female approach to determining ethical ideals is not only desirable but required by precedent within Maori ethics. It is tika (appropriate or correct) for Maori women to follow in the steps of their ancestresses and those who do so will In turn be remembered, their deeds related, identifiable as ethical models. The publicly held principle of conjoining morality and spirituality as an exclusively male concern may be an ethical interpretation, but not an appropriate one, as evidenced by the concept, mana wahine Maori.
Keywords: Maori women